Movement behaviour of the Green Jobfish (Aprion virescens), the Potato Bass (Epinephelus tukula) and the Giant Trevally (Caranx ignobilis), on South Africa's coral reefs - Logan, Guy (Centre for Supramolecular Chemistry Research, 2025)
The movement behaviour of three important reef fish predators, namely potato bass (Epinephelus tukula), green jobfish (Aprion virescens) and giant trevally (Caranx ignobilis), were studied to provide information for marine spatial planning and to understand their ecological roles on South Africa's coral reefs. The three species were expected to display contrasting movement behaviour and to place different demands on spatial management strategies. The three species of coral reef meso-predators, potato bass (n=35), green jobfish (n=38) and giant trevally (n=9) were tagged with acoustic transmitters and released within a widespread receiver array (n=46) spanning approximately 306 km of coastline, which included the iSimangaliso Wetland Park (IWP), South Africa, and Ponta do Ouro Partial Marine Reserve (PPMR), Mozambique. The resulting telemetry data were used to investigate (1) the extent of their movements, (2) temporal patterns of movement, and (3) movements and connectivity between different management zones within the IWP, South Africa's largest coastal marine protected area. An analysis of 892 552 detections over a period of six and a half years, using a novel residency index, showed that green jobfish and potato bass exhibit high site fidelity with residency index values ranging from 61.6 to 100 % (mean = 85.2 %) for green jobfish and from 87.3 to 99.9 % (mean = 95.0 %) for potato bass. Individual green jobfish and potato bass were detected at a similar number of receivers (mean 3 [± 0.4] and 3.3 [± 0.8]), respectively. In contrast, giant trevally had lower site fidelity with residency index values ranging from 49.4 to 92.3 % (mean = 66.9 %) and undertook frequent but temporally predictable long-distance migrations (mean maximum dispersal distance = 189.00 km [± 40.3]), often returning to their home range. On average individual giant trevally were detected on 13.8 (± 1.5) receivers. Previous literature showed variable temporal patterns of movement for green jobfish although the results of this study showed no evidence of cyclical patterns of movement, further investigation would be required to confirm this result. Potato bass exhibited both 12 hr and 24 hr temporal patterns with the 12 hr pattern appearing indicative of tidally influenced cyclic movement and 24 hr patterns appear to indicate diel patterns. Giant trevally were almost exclusively detected during the day when present on the reefs, but left their home reefs on predictable summer migrations to a known aggregation site in Mozambique as observed by Daly et al. 2019. Green jobfish and potato bass crossed an average of 0.6 (± 0.9 and 0.4) management zones (mean zone length 22.5 km [± 4.1]) per tagged fish compared to giant trevally, that crossed on average 2.4 (± 0.9) management zones per tagged fish in the IWP. Border crossings between South Africa and Mozambique were observed in all three species, two from green jobfish and three from potato bass, and all five detected giant trevally. Green jobfish and potato bass with significant detections (>100) appeared to undertake little to no movement beyond their home range, reef and zone. No migratory or aggregatory behaviour was identified, possibly indicating localised spawning aggregations on each reef complex/zone. Therefore, current MPA size (10 700 km2) should provide complete protection of green jobfish and potato bass within sanctuary zones of the IWP. Giant trevally appeared to be adequately protected within sanctuary zones of the IWP but are vulnerable during summer spawning migrations north, to Mozambique. A closed season during this migratory period could help safeguard giant trevally and ensure the greatest chance of them reaching the aggregation site. This interzonal connectivity should be considered when updating management plans of each zone within the IWP, the PPMR, future marine protected areas and the management of the species themselves.